2010
DOI: 10.1007/s11998-010-9253-6
|View full text |Cite
|
Sign up to set email alerts
|

In situ XRD characterization of hydrogen desorption from electrochemically deposited Pd coating

Abstract: One of the main problems in electrochemical Pd deposition of coatings is the hydrogen desorption that causes microcracking phenomena. With the aim of understanding the structural changes due to the hydrogen desorption, the kinetics of the phase transformation from hydride to metallic structure has been followed by in situ X-ray diffraction (XRD) experiments. The structural evolution of samples obtained by two different electrochemical baths has been compared. It was found that the solubility and the desorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…By controlling the potential or current density of an electrochemical cell, deposition occurs from an oxidized form in solution to a metallic state at the surface. The most straightforward is the synthesis of interstitial hydrides, such as palladium hydride by using various electrochemical baths …”
Section: Synthetic Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…By controlling the potential or current density of an electrochemical cell, deposition occurs from an oxidized form in solution to a metallic state at the surface. The most straightforward is the synthesis of interstitial hydrides, such as palladium hydride by using various electrochemical baths …”
Section: Synthetic Routesmentioning
confidence: 99%
“…The most straightforward is the synthesis of interstitial hydrides, such as palladium hydride by using various electrochemical baths. 244 The synthesis of Mg NPs has also been reported through the electrochemical reduction of organomagnesium compounds. Haas and Gedanken proposed a sono-electrochemical synthetic approach to prepare 4 nm magnesium NPs deposited at the tip of a sonicating probe with ethyl-and butylmagnesium chloride as magnesium precursors.…”
Section: Thin Film Synthesesmentioning
confidence: 99%
“…This mechanism is reversible, in the air is observed the hydrogen desorpion from palladium. The conductance of metallic palladium is higher than palladium hydride conductance and therefore creation of PdH x results in resistance increase [17][18][19][20].…”
Section: C-pd Films As Hydrogen Sensorsmentioning
confidence: 99%
“…Furthermore, recent research has demonstrated that in situ x-ray diffraction can be utilized to monitor hydrogen absorption and release in nano-sized Pd crystals. By observing dynamic phase transitions, researchers can gain valuable insights into the behavior of hydrogen in these materials, which is crucial for understanding their applications in various fields [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%